THE EFFECT OF THE GIVING QUESTION GETTING ANSWERS MODEL THROUGH EXPERIMENTAL METHODS ON PHYSICS MOTIVATION AND LEARNING OUTCOMES - Yulianti, Farizah; Sutrio, Sutrio; Sahidu, Hairunisyah (Lensa: Jurnal Kependidikan Fisika, 2019)
The aim of this research is to know the impact of the applying Giving Question Getting Answers model with experimental methods toward the learning motivation and result of physics learning. The type of research used was quasi-experimental with posttest only control group design. The population was all student of grade XI in senior high school 1 of  Labuapi. The sampling technique used saturation sampling, while the sample are class XI MIA 1 as the experimental 1 class, and the XI MIA 2 as experimental 2 class. Experimental 1 class was treated with giving question getting answers learning model with experimental methods and experimental 2 class was treated with giving question getting answers learning model without experimental methods. The instrument of motivation learning was used motivation questionnaire and instrument the result of physics learning used multiple choice test. The research hypothesis was tested using Manova-test, data analysis shows that Sig. <0,05 which mean that H0 was rejected and Ha accepted. Thus, it can be concluded that there are effect of Giving Question Getting Answers model with experimental methods on student?s motivation and physics learning result.